Rivastigmine decreases brain damage in HIV patients with mild cognitive deficits. Issue 12 (7th November 2017) - Perrotta, Gaetano; Bonnier, Guillaume; Meskaldji, Djalel‐Eddine; Romascano, David; Aydarkhanov, Ruslan; Daducci, Alessandro; Simioni, Samanta; Cavassini, Matthias; Metral, Melanie; Lazeyras, François; Meuli, Reto; Krueger, Gunnar; et al.
Abstract: Rivastigmine has been shown to improve cognition in HIV+ patients with minor neurocognitive disorders; however, the mechanisms underlying such beneficial effect are currently unknown. To assess whether rivastigmine therapy is associated with decreased brain inflammation and damage, we performed T1/T2* relaxometry and magnetization transfer imaging in 17 aviremic HIV+ patients with minor neurocognitive disorders enrolled on a crossed over randomized rivastigmine trial. Rivastigmine therapy was associated with changes in MRI metrics indicating a decrease in brain water content (i.e., edema reabsorption) and/or reduced demyelination/axonal damage. Furthermore, MRI changes correlated with cognitive improvement on rivastigmine therapy.